Contraceptive Methods and the Impact of Menstruation on Daily Functioning in Women with Sickle Cell Disease. Issue 3 (March 2019) - Day, Melissa E.; Stimpson, Sarah-Jo; Rodeghier, Mark; Ghafuri, Djamila; Callaghan, Michael; Zaidi, Ahmar Urooj; Hannan, Bryan; Kassim, Adetola; James, Andra H.; DeBaun, Michael R.; Sharma, Deva
Abstract: Objectives: Women with sickle cell disease (SCD) are living longer as a result of advances in the care of their underlying disease. With the population growing of women living with SCD, reproductive health issues in this population have become an emphasized area of medical care. We sought to describe current patterns of contraception use, menstruation, and quality-of-life (QOL) measures in women with SCD. Methods: Using a cross-sectional study design, we administered paper surveys at two academic medical centers to women aged 10 to 55 years with SCD to capture current contraceptive use, characteristics of menstrual cycles, and QOL metrics. Results: Of the 103 women who participated, 12.7% (13/102) experienced a duration of menses >7 days (defined here as prolonged menstrual bleeding). Approximately half of women (51.5%, 53/103) used some form of contraception, with depot medroxyprogesterone acetate injections and condoms being the most common. During their last menstrual periods, women with both dysmenorrhea and prolonged menstrual bleeding (6.9%, 7/102) were more likely to experience more days of poor QOL, with more nights with sleep disturbance ( P = 0.001) and more days with trouble taking care of themselves ( P = 0.003), as well as being unable to do things they previously enjoyed ( P = 0.001), compared with those with neither phenomenon (28.2%, 29/103). Conclusions: Dysmenorrhea and prolonged menstrual bleeding negatively affect the QOL of women with SCD. Menstrual histories and preventive measures for menstruation-related morbidity should be incorporated into routine evaluations of women with SCD. Abstract : As women with sickle cell disease live longer, understanding women's health issues and their impact on quality of life has become of increasing importance. The authors describe the present use of contraceptive methods (both hormonal and nonhormonal) and the impact of dysmenorrhea and prolonged menstrual bleeding on daily functioning in a cross-sectional study of women with sickle cell disease.Supplemental digital content is available in the text.